2023
DOI: 10.56294/cid202382
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preventive and Mandatory Social Isolation in the control of type I diabetes in adults in the Buenos Aires Metropolitan Area

Maria Isabel Morgner,
Lorena Djament

Abstract: Introduction: The measures taken by the Argentine government to avoid contagion of the SARS-CoV-2 virus consisted in what was called Preventive and Mandatory Social Isolation (Aislamiento Social Preventivo y Obligatorio, ASPO), which was established on March 20th of 2020. The disposition restricted medical checkups and physical activity for several months and modified the population’s eating habits. Diabetes Mellitus (DM) is a high incidence and prevalence pathology worldwide. While the majority of the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…(40) También se menciona el uso de minería de datos como técnica y redes neuronales en sistemas de tutoría inteligente para brindar orientación e instrucción adaptativas a los estudiantes. (41) Estos hallazgos resaltan la utilidad del machine learning en identificar y abordar problemas de aprendizaje de manera temprana. En la categoría de mejora en la gestión educativa, se encontró que el gobierno estatal tiene un impacto significativo en el rendimiento académico, mientras que el gobierno no estatal está relacionado con niveles más altos de rendimiento.…”
Section: Resultados Y Discusión ¿En Qué Contexto Educacional Se Imple...unclassified
“…(40) También se menciona el uso de minería de datos como técnica y redes neuronales en sistemas de tutoría inteligente para brindar orientación e instrucción adaptativas a los estudiantes. (41) Estos hallazgos resaltan la utilidad del machine learning en identificar y abordar problemas de aprendizaje de manera temprana. En la categoría de mejora en la gestión educativa, se encontró que el gobierno estatal tiene un impacto significativo en el rendimiento académico, mientras que el gobierno no estatal está relacionado con niveles más altos de rendimiento.…”
Section: Resultados Y Discusión ¿En Qué Contexto Educacional Se Imple...unclassified
“…This approach could have significant implications in clinical practice by early identification of patients who will respond favorably to FMT. (32,33,34,35,36,37,38,39,40,41,42,43,44) Regarding methodological limitations and errors, it is important to recognize that most of the studies included in this review are observational and that the quality of evidence could be improved with high-quality randomized clinical trials. In addition, more rigorous standardization of FMT protocols is needed to ensure comparability of results across studies.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 45,45 % of the reviews indicated aspects of clinical management such as the availability of information on the patient's status immediately through the electronic medical history record. (33,34,35,36) In addition to the management of food to the nutrition service in the cases of hospitalized users and the follow-up and compliance with the clinical tasks indicated by the attending physician on a day-to-day basis to the multidisciplinary health team such as students in training. (37,38,39,40,41) https://doi.org/10.56294/sctconf2023455…”
Section: Results On the Impact Of Electronic Medical Records On Healt...mentioning
confidence: 99%
“…Similarly, Wali et al (2020) (61) state that improving the doctor-patient relationship using the electronic health record improves the quality of services and the user saves time for other activities. Finally, for Tran et al ( 2020), (26) the implementation of a medical record application is feasible, acceptable and viable for the collection of user data, as it is a reliable tool and, above all, easier to use than traditional paper, maintaining the confidentiality of the patient's data, even more so, giving them confidence in their treatment plan and Maia Chade et al ( 2019), (35) and Kim et al (2020) (36) indicate that the work efficiency of medical interns and improving the workflow within clinical management. There is no doubt that the impact of the use of the EHR is beneficial for all the actors involved in the care and health management process.…”
Section: Comparative Results Of the Impact Of Electronic And Traditio...mentioning
confidence: 99%